Becoming natural: the naturalization of synthetic flavors in the twentieth century and the introduction of Konsumstoff - Gennermann, Paulina (Berichte zur Wissenschaftsgeschichte, 2023)
Is it possible that non-natural chemical substances become natural without changing their chemical, physical or physiological characteristics? The history of synthetic flavors with a special emphasis on vanillin suggests that yes, it is possible. This process is called naturalization and means in this case the change of status of a synthetic flavor to something natural. In this article the history of vanillin as a frequently used flavor and its transformation into a natural ingredient in the twentieth century will be presented and analyzed. Studying the particular characteristics of vanillin, it seems that known concepts in the history of science like Ersatzstoff (surrogate) or Wirkstoff (active agent) do not constitute the best fit in describing this flavoring agent. Categorizing vanillin as a Konsumstoff (commodity agent) seems more useful in order to classify its characteristics and its historical development. I suggest using Konsumstoff as a new theoretical and methodological approach to study the history of chemical substances. In this article, the concept of Konsumstoff will be outlined and developed using the vanillin case as a paradigmatic example.
Zuerst veröffentlicht: 18. Oktober 2023
Gesehen am 18.12.2023